2017
DOI: 10.1002/jbm.b.34036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet‐rich plasma on biological activity and bone regeneration of brushite‐based calcium phosphate cement

Abstract: In this study, we focused on identifying the effects of platelet-rich plasma (PRP) on bioactivity and bone ingrowths incorporated into brushite cement. We introduced PRP as a series of substitutions with an aqueous citrate-ion solution, and the optimized cement with PRP showed no disintegration of the paste consistency. Incorporating PRP showed that the setting time decreased with the increasing of PRP ratios, although the compressive strength was not significantly changed. We evaluated in vitro degradation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…The coagulation system of the human body was mainly composed of two main pathways, the endogenous coagulation pathway, and the exogenous coagulation pathway 34 . They produced coagulation factor X that could activate during hemostasis, using positive feedback regulation to initiate coagulation, enhance the initial thrombin activity, and expand the cascade effect to accelerate the coagulation process 35 . The clinical significance of APTT refers to the process in which the plasma to be tested converts fibrin into insoluble fibrin under the action of the coagulation factor calcium ions, which represented the endogenous coagulation pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coagulation system of the human body was mainly composed of two main pathways, the endogenous coagulation pathway, and the exogenous coagulation pathway 34 . They produced coagulation factor X that could activate during hemostasis, using positive feedback regulation to initiate coagulation, enhance the initial thrombin activity, and expand the cascade effect to accelerate the coagulation process 35 . The clinical significance of APTT refers to the process in which the plasma to be tested converts fibrin into insoluble fibrin under the action of the coagulation factor calcium ions, which represented the endogenous coagulation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…34 They produced coagulation factor X that could activate during hemostasis, using positive feedback regulation to initiate coagulation, enhance the initial thrombin activity, and expand the cascade effect to accelerate the coagulation process. 35 The clinical significance of APTT refers to the process in which the plasma to be tested converts values of all samples were lower than those of the control group, with significant differences, indicating that the materials promote coagulation through the endogenous coagulation pathway. We found that there was no regularity among APTT data, and 4Ce-MBG had the lowest APTT data.…”
Section: Whole Blood Clotting Ability In Vitro Hemostasis Assay and P...mentioning
confidence: 99%
“…The in vivo study revealed the potential bone‐regeneration properties of the microspheres, which provided extensive support for host‐cell migration and proliferation. The calcium ion and degradation products produced a compatible fluidic environment for the interaction between host cells and microspheres and allowed integration of cells into the microspheres. The CSD‐deficient SA‐1 microsphere delayed bone consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand white rabbits implanted with platelet-rich plasma-enhanced CPC had higher BV/TV and degradation rate after four weeks. Histological findings showed the recruitment of fibrous tissues at the early stage of implantation, which later disappeared to facilitate bone formation [ 69 ]. In female ovariectomised rats with a cavity-like defect at the distal 1/3 of the caudal vertebral body, the augmentation of CPC with platelet-rich plasma as filler material improved trabecular bone microstructure, BMD, new bone formation, and osteogenesis grade as compared to those implanted with CPC only [ 1 ].…”
Section: The Enhancement Of Cpcmentioning
confidence: 99%